Introduction by the Editor - Capistrano, Erik Paolo S. (Philippine Management Review; Vol 30 (2023), 2023)
The Philippine Management Review (PMR) is the academic journal publication of the University of the Philippines Cesar E.A. Virata School of Business. It is a venue where academics from the various business and economics disciplines share rigorous researches and commentaries on relevant issues in their respective domains. In keeping with this long-standing tradition of delivering diverse scientific and logical perspectives and recommendations involving major business and economic issues, the 2023 edition of the PMR presents five articles on human resources, behavioral finance, corporate governance, and corporate finance. However, beyond these domains, each of these studies also present significant social implications. Each of these studies recognize that the world is changing, challenging existing norms.